KONSEP LARANGAN (نهي) SEBAGAI ALAT PENDIDIKAN MENURUT ALQURAN - Khairurrijal Khairurrijal (Edu Global : Jurnal Pendidikan Islam, 2021)
the theories and concepts of educatin as a whole to form a human personality who has faith and has noble character. The concepts discussed include educational tools that can be applied to achieve educational goals. Educational tools are an important element in realizing education. Prohibition as a preventive educational tool can prevent humans from commiting despicable acts and immoral acts in life. Alquran as a guide and guidance in all aspectsof human life. In the Quran there is much discussion about prohibition as an educational tool related to faith, worship, morals, and social interaction. The concept of prohibition is discussed implicitly so that it can be understood using a theoretical approach in the concept of education that prohibition includes non-object educational tools in educational theory.